Insects as fruit pollenators - Boys, William Armfield (My University, 1904)
Introduction: There has perhaps been an idea quite prevalent among the majority of people for ages past that color, fragrance and all that is pleasing in flowers to the senses of man were created for his enjoyment. Christian Conrad Sprengel seems to have been the first to take a different view, of the subject. In 1787 he discovered that in most flowers that contain nectar it is so located that incests may have easy access to it and that at the same time it is protected from destruction by rain, and he concluded "that the nectar of these flowers is secreted for the sake of insects and is protected from rain in order that the insects may get it pure and unspoiled." He also observed that there were certain markings near the nectaries which he concluded were pathfinders or honey guides. This led to the conception that if these markings were to lead the insect to nectaries then the color of the flowers was first to attract the insect to the flower; Although his conslusions as to the importance of cross-fertilization in plants were rather meager, as later investigations has revealed, he was the means of starting observations which were carried on by others in later years that have given more established facts. There has been much study on the relation of insects to flowers in cross-pollenization on since the time of Sprengel. As it has been demonstrated that there is a decided benefit to plants in cross-pollenization…
Citation: Boys, William Armfield. Insects as fruit pollenators. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Insects; Pollenation; Fruit Pollenation; Theses